High-coercivity heavy-rare-earth-free NdFeB sintered magnets developed by doping Ce85Al15 and grain boundary diffusion with Pr70Cu15Al15 - Y. J. Wong; H. W. Chang; Y. I. Lee; W. C. Chang; C. H. Chiu; C. C. Mo (AIP Advances, 2023)
Traditional NdFeB sintered magnets with coercivity larger than 20 kOe, called super-high (SH) level, usually contains considerable amount of high-cost heavy rare earth (HRE), such as Dy or Tb. In this work, high coercivity of 21.4 kOe, which corresponds to SH level, is achieved for HRE-free NdFeB magnet by doping with Ce85Al15 (CeAl) alloy and grain boundary diffusion (GBD) with Pr70Cu15Al15 (PrCuAl) alloy powders, where Ce/RE ratio is about 15% within the magnet. After GBD treatment with PrCuAl on Ce-containing NdFeB magnets, the formation of Pr-containing shell at 2:14:1 grain surface can increase the local magnetic anisotropy filed and therefore enhance the coercivity. Most of Cu and Al, and parts of Ce and Pr appear at grain boundary and triple junction, which can reduce the magnetization of grain boundary phase, strengthen the decoupling effect between grains and thus contribute to high coercivity. This study provides a cost-effective way to obtain high coercivity for HRE-free NdFeB sintered magnet via doping Ce85Al15 and then GBD with Pr70Cu15Al15.